Evaluating Lecturer Satisfaction on Academic Information System Using Usability and EUCS at Bandung University of Technology - Sela Octaviani; Evi Triandini; Dandy Pramana Hostiadi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
Academic Information Systems play a crucial role in supporting academic data management, administrative processes, and informed decision-making within higher education institutions. Despite their widespread adoption, the extent to which these systems effectively meet the needs and expectations of lecturers, their primary users, remains insufficiently explored. Understanding user satisfaction is critical, as it directly influences system acceptance, continued usage, and overall institutional performance. This study aims to evaluate lecturer satisfaction with Academic Information Systems at Bandung University of Technology by integrating two complementary evaluation methods, the System Usability Scale and End User Computing Satisfaction. The integration of these methods enables a more holistic assessment by combining usability measurements with multidimensional user satisfaction indicators. The findings reveal an exceptionally high SUS score of 99.94, classified as Best Imaginable, indicating that lecturers perceive the system as highly usable, intuitive, and supportive of their academic tasks. The EUCS analysis identifies Accuracy, Format, and Ease of Use as significant factors influencing lecturer satisfaction. These variables demonstrate the importance of accurate and reliable information, a well-structured interface, and system features that facilitate efficient task completion. The combined results highlight specific areas requiring strategic improvement, particularly in maintaining data accuracy, enhancing interface design consistency, and strengthening overall usability to accommodate users’ academic workflows. Theoretically, it demonstrates the added methodological robustness gained from combining SUS and EUCS in evaluating academic information systems, thereby ensuring more substantial alignment with user